Can community-based signalling behaviour in Saccharomyces cerevisiae be called quorum sensing? A critical review of the literature. Issue 5 (4th July 2019) - Winters, Michela; Arneborg, Nils; Appels, Rudi; Howell, Kate
ABSTRACT: Quorum sensing is a well-described mechanism of intercellular signalling among bacteria, which involves cell-density-dependent chemical signal molecules. The concentration of these quorum-sensing molecules increases in proportion to cell density until a threshold value is exceeded, which triggers a community-wide response. In this review, we propose that intercellular signalling mechanisms can be associated with a corresponding ecological interaction type based on similarities between how the interaction affects the signal receiver and producer. Thus, we do not confine quorum sensing, a specific form of intercellular signalling, to only cooperative behaviours. Instead, we define it as cell-density-dependent responses that occur at a critical concentration of signal molecules and through a specific signalling pathway. For fungal species, the medically important yeast Candida albicans has a well-described quorum sensing system, while this system is not well described in Saccharomyces cerevisiae, which is involved in food and beverage fermentations. The more precise definition for quorum sensing proposed in this review is based on the studies suggesting that S. cerevisiae may undergo intercellular signalling through quorum sensing. Through this lens, we conclude that there is a lack of evidence to support a specific signalling mechanism and a critical signal concentration of these behaviours in S. cerevisiae, and, thus, these features require further investigation. Abstract : Does Saccharomcyes cerevisiae really undergo quorum sensing?